TEKNOLOGI PENGENDALIAN HAYATI HAMA PENGHISAP PUCUK DAN BUNGA PADA JAMBU METE - ., Samsudin; Trisawa, Iwa Mara (Pusat Penelitian dan Pengembangan Perkebunan, 2011)
Technology in controlling of sucking pest of shoot and flowers on cashew. The major pests of cashew plant (Anacardium occidentale L.) are Helopeltis spp.Â and Sanurus spp. A number of cashew trees damaged beÂ attacked by the pest are increasing from year to year. Some research found on effectiveness technologies, environmentally friendly and easily adopted by farmers have been done. One kind of controlling technologies that provides great expectations to be developed by farmers was biological control by utilizing parasitoids, predators and pathogens. Development of rangrang ants (Oecophylla smaragdina) and the fungus Beauveria bassiana as biological agent of Helopeltis spp. on a large scale will suppress the population of the insects. Meanwhile, the egg parasitoid Aphanomerus sp., moth parasitoids Epieurybrachys nsp. and the fungus Synnematium sp. are potentially developed as a biological control agents for Sanurus spp. in the field. The results of these studies should be integrated as a technology package on which the farmers should be involved in implementation of the technology.